Structure and Properties of Double Perovskite System La\(_2\)Co\(_1-x\)Fe\(_x\)MnO\(_6\) - Tan, Pham The; Yen, Pham Huyen; Nhat, Hoang Nam; Hoa, Nguyen Quang (Communications in Physics, 2014)
Low Fe-doped insulating ferromagnets La_2CoMnO_6 were prepared and studied. The compounds crystallized in orthorhombic space group Pnma with slight changes in the lattice constants. We have observed a significant reduction of resistivity due to doping, together with an increase of magnetization and saturated magnetization as doping level increased. The doping also reduced T_C for both transitions at around 220 and 140 K which attribute for the different spin orderings of the magnetic ions. The small features were also seen at around 40 K and should correspond to the cluster glassy region with spin disorders.